2013
DOI: 10.3402/rlt.v21i0.19153
|View full text |Cite
|
Sign up to set email alerts
|

Combining the formative with the summative: the development of a twostage online test to encourage engagement and provide personal feedback in large classes

Abstract: The aim of this action research project was to improve student learning by encouraging more ''time on task'' and to improve self-assessment and feedback through the introduction of weekly online tests in a Year 2 lecture module in biological sciences. Initially voluntary online tests were offered to students and those who participated achieved higher exam marks than those who did not, but completion rate was low. Making the tests compulsory led to high completion rates, but class performance decreased, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 35 publications
1
20
0
4
Order By: Relevance
“…These results support our hypothesis that collaborative enquiry-based learning and educational opportunities provided by handheld devices for formative assessment led to a significantly better exam performance for the students who took PeLe quizzes, compared to those who did not. The summative part of PeLe tests ensured a high completion rate, whereas the formative part provided students with prompt feedback and gave them information on what they needed to do to improve their performance (Voelkel, 2013). The increase in the overall exam results was encouraging, but not conclusive enough to show that only PeLe tests were beneficial.…”
Section: Cyclementioning
confidence: 88%
See 1 more Smart Citation
“…These results support our hypothesis that collaborative enquiry-based learning and educational opportunities provided by handheld devices for formative assessment led to a significantly better exam performance for the students who took PeLe quizzes, compared to those who did not. The summative part of PeLe tests ensured a high completion rate, whereas the formative part provided students with prompt feedback and gave them information on what they needed to do to improve their performance (Voelkel, 2013). The increase in the overall exam results was encouraging, but not conclusive enough to show that only PeLe tests were beneficial.…”
Section: Cyclementioning
confidence: 88%
“…Recent research has demonstrated the variety of educational benefits mobile technologies have for foreign language learning/teaching, including: an increase in learner autonomy (Murphy, Bollen, & Langdon, 2012); mobile networking collaboration (Lan, Sung, & Chang, 2007;Pemberton, Winter, & Fallahkhair, 2010); new formats for problem-solving, interactive tasks based on augmented reality (Cook, 2010;Driver, 2012); a more personalized learning experience (Petersen & Markiewicz, 2008;Oberg & Daniels, 2013); instant feedback (Voelkel & Bennett, 2013); immediate diagnosis of learning problems and design of new assessment models (Cooney & Keogh, 2007).…”
mentioning
confidence: 99%
“…Educational materials must not only actively engage and resonate with the learner, but also encourage him or her to seek mentorship and the support of his or her peers [2223]. Best practices incorporate a variety of interactive strategies to accommodate the multiple learning styles, skills, and experiences of the adult learners [21, 24]. In addition, a well-designed online program must demand time on task and communicate high expectations for the learners.…”
Section: Factors and Information That Shape The Onp Curriculummentioning
confidence: 99%
“…The challenge of providing inclusive, engaging and formative feedback to students on their assessments is an area of import for many educators in higher education regardless of the mode of delivery-online or face-to-face (Nicol & Macfarlane-Dick, 2006;Voelkel, 2013). Some traditional methods for formative feedback such as written comments can be perceived as very time consuming by the marker and raises the dilemma of quality feedback versus timely feedback (Wallace & Moore, 2012).…”
Section: Strategies For Inclusive Formative Feedbackmentioning
confidence: 99%